EFFECT OF PRIMARY PROCESSING PRACTICES CARRIED OUT BY THE COFFEE COOPERATIVE SOCIETIES ON THE SUSTAINABILITY OF THE COFFEE INDUSTRY IN KENYA - Mwangi, Regina Wambui; Mwenda, Dr. Lilian Karimi Mugambi; Wachira, Dr. Anita Wanjugu; Mburu, Dr. David Kiarie (European Journal of Business and Strategic Management, 2017)
Purpose: The study sought to analyze the effect of primary processing practices carried out by the coffee cooperative societies on the sustainability of the coffee industry in Kenya. Methodology: The study adopted descriptive research design. From a target population of 525 coffee cooperative societies in the East and West of the Rift valley, a sample size of 295 coffee cooperative societies was drawn using stratified random sampling where the response rate was 82.71 percent. The chair persons were the key respondents. A cross sectional survey was conducted where the self-administered questionnaire. Collected data was analyzed using descriptive and inferential statistics. Results: The results showed that the primary processing practices and sustainability of the coffee industry are positively and significantly related. Using the regression of coefficient, the primary processing practices had a beta value of 0.462 with a t-value of 4.21 and p=0.000. Since p is <0.05, the null hypothesis was rejected at a significant level of 0.05. Unique contribution to theory, practice and policy: The study recommended that there is need to invest heavily on training of employees for effective primary processing in a bid to boost the sustainability of the coffee industry. Further in order to boost the sustainability of the coffee industry, the study recommends that the coffee cooperative societies should engage in appropriate drying of the parchment coffee, invest in machinery for wet processing and use sustainable sources of energy. This improves the gross profit of the small scale coffee farmers, hence boosting sustainability of the coffee industry